Smart Hajj and Umrah: Inovasi Manajemen Digital Untuk Pelayanan Jama’ah di Era Modern - Chairawati, Fajri; Nadia Islami, Rosa (Al-Mabrur: Jurnal Manajemen Haji dan Umrah, 2026)
Hajj and Umrah pilgrim services are highly complex, requiring adaptive and efficient management innovations. This study aims to examine the implementation of the Smart Hajj and Umrah concept, which integrates digital technologies such as big data, artificial intelligence, and the Internet of Things into pilgrim management. The research method employed is a qualitative approach using descriptive analysis based on literature reviews and digital technology policy analysis. The results indicate that digital innovations enhance the efficiency, safety, and comfort of services; however, they face challenges such as pilgrims’ digital literacy, infrastructure limitations, and data security issues. Optimization strategies include improving digital literacy, strengthening infrastructure, fostering cross-sector collaboration, and adopting a human-centered approach to technology. This study provides recommendations for the development of inclusive and sustainable digital management of Hajj and Umrah.